2018
DOI: 10.1002/pen.24953
|View full text |Cite
|
Sign up to set email alerts
|

Wall Slip of Linear Polymer Melts During Ultrasonic‐assisted Micro‐injection Molding

Abstract: The wall slip of linear polymer melts under ultrasonic vibration is investigated by correcting the slip mechanism, and melt flow behaviors in ultrasonic‐assisted micro‐injection molding (UμIM) method are discussed. Based on the effect mechanism of ultrasonic vibration on the melt, theoretical models of the critical shear stresses for the onset of weak and strong wall slip during UμIM are established, and the change in rheological properties due to the onset of wall slip under ultrasonic vibration is experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…It is known that the use of ultrasound in the processing of polymers is accompanied by the breaking of chemical bonds of macromolecules (mechanochemical destruction), which in turn leads to a decrease in the molecular weight of polymers. Similar processes have been also observed with other types of damage, including in the process of multiple polymer processing (mechanical destruction) [11][12][13][14][15][16]5].…”
Section: Original Research Articlesupporting
confidence: 57%
“…It is known that the use of ultrasound in the processing of polymers is accompanied by the breaking of chemical bonds of macromolecules (mechanochemical destruction), which in turn leads to a decrease in the molecular weight of polymers. Similar processes have been also observed with other types of damage, including in the process of multiple polymer processing (mechanical destruction) [11][12][13][14][15][16]5].…”
Section: Original Research Articlesupporting
confidence: 57%
“…Ultrasonic processing technology, as a novel molding processing technology, has been widely used in recent years for the injection molding, extrusion molding, and compression molding of polymers [9,10]. Despite different ways of applying ultrasonic energy, studies have found that ultrasounds can affect the microstructure filling performance [11], change the material properties [12], affect the extrusion swelling [13], improve the weld line strength of the plastic parts [14], and reduce the interface friction during ejection [15].…”
Section: Introductionmentioning
confidence: 99%
“…Third, the corrosion on the microcavity wall caused by cavitation damage and high frequency impact of melt under the effect of ultrasonic vibration promoted the nucleation type with the wall microstructure as the crystal nucleus [25]. Finally, during the propagation of ultrasonic vibration in the polymer melt, the internal friction and collision of polymer chains led to a heating effect on the melt, which could increase the nucleation rate [26]. Therefore, in summary, the crystallization rate of the semi-crystalline polymer was increased by ultrasonic vibration in LUμIM process.…”
Section: Resultsmentioning
confidence: 99%